2010
DOI: 10.4103/0028-3886.63793
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low dietary calcium intake in patients with epilepsy: A study from South India

Abstract: The dietary consumption of calcium of all the patients was far below the recommended daily dietary allowance (RDA) by Indian Council of Medical Research (ICMR). Low dietary calcium could have a confounding effect on PWE on AED in all age groups. There is a need to formulate consensus guidelines to supplement dietary calcium to PWE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…35 To date, there are only a few studies in Italy, the United States, and India that have assessed nutritional intakes in children with epilepsy. [37][38][39] These studies have shown that children with intractable epilepsy are at risk of poor nutritional status with decreased nutritional intake, and our study reaffirms this. Despite vitamin D and calcium intake not appearing to be a risk factor for 25(OH)D deficiency in our study, knowledge that a high proportion of Malaysian children with epilepsy have poor nutritional intake is invaluable.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…35 To date, there are only a few studies in Italy, the United States, and India that have assessed nutritional intakes in children with epilepsy. [37][38][39] These studies have shown that children with intractable epilepsy are at risk of poor nutritional status with decreased nutritional intake, and our study reaffirms this. Despite vitamin D and calcium intake not appearing to be a risk factor for 25(OH)D deficiency in our study, knowledge that a high proportion of Malaysian children with epilepsy have poor nutritional intake is invaluable.…”
Section: Discussionsupporting
confidence: 85%
“…This is significantly lower when compared to a previous Malaysian study, which showed that approximately 50% of Malaysian children did not achieve the recommended vitamin D and calcium intake . To date, there are only a few studies in Italy, the United States, and India that have assessed nutritional intakes in children with epilepsy . These studies have shown that children with intractable epilepsy are at risk of poor nutritional status with decreased nutritional intake, and our study reaffirms this.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, vitamin D and calcium are responsible for bone and mental health, and patients treated with antiepileptic drugs are particularly vulnerable to osteoporosis and depression [55]. Other studies have shown low calcium intake by patients with epilepsy [56]. The study also showed signi cantly lower vitamin C and potassium and higher sodium intakes by epileptics.…”
Section: Discussionmentioning
confidence: 81%
“…The 19th century which was known as the "Biological Era", studies on metabolism and chemistry were done, helping the science of nutrition on defining their role in the development and prevention of chronic diseases, such as cancer, cardiovascular, neurodegenerative, and bone metabolism disorders [21]. Throughout the 20th century, Nutritional Science focused on finding vitamins [23] and minerals [24], defining their use and preventing the deficiency diseases [25][26][27][28] that they caused. Later, nutrition related health problems of the developed world shifted to over nutrition, obesity [29] and type-2 diabetes [30,31], the focus of modern medicine and of Nutritional Science changed.…”
Section: Originmentioning
confidence: 99%